Analisis Balance Cairan Pada Anak Diare Setelah diberikan Pemenuhan Kebutuhan Cairan di Ruangan Perawatan Anak Rsud. Prof. Dr. H. Aloei Saboe Kota Gorontalo - Andi Akifa Sudirman; Dewi Modjo; Rivaldy Mokodompit (Universitas Katolik Widya Karya Malang, 2023)
Diarrhea in children is a health problem with a high mortality rate, especially in children aged 1 to 4 years. The main cause of death is dehydration due to loss of fluids and electrolytes through feces, so it is important to fulfill fluid needs to replace and meet fluid needs in children with diarrhea. The purpose of this study was to be able to analyze the fluid balance in children with diarrhea after being given fluid needs at the hospital. Prof. Dr. H. Aloei Saboe, City of Gorontalo. This research is a descriptive quantitative research and uses a pre-experimental design with the type of one group pre-post test. with a sample of 2 children with diarrhea. with accidental sampling technique. Data analysis used a nursing care case report approach then data analysts, the data collected is associated with relevant concepts, theories, principles. The results of this study indicate that there is an increase in fluid balance in children who experience diarrhea after being given fluids to meet their needs.